A Survey on Data Mining using Genetic Algorithm - Khatoon, Mariya; Agarwal, Abhay Kumar (International Journal of Computer Sciences and Engineering, 2019)
Growth in the field of data mining rapidly increasing due to its well regulated techniques and efficient algorithms. At present, Genetic algorithm is the bustling research and it allocate the drastic modification in the field of data mining in terms of better optimization of result and the performance of different ventures effectively and efficiently. Because of their accuracy and efficiency, data mining algorithms attract and motivates to researchers to show interest in their technologies and large search space. Genetic algorithm works on bio-responsive operators to evaluate the fittest function in population by the Darwinism. This paper enumerates the enactment of genetic algorithm in frame of reference to data mining algorithms and techniques like decision tree and classification. The main objective of this paper is describes the application and benefits of different data mining techniques related to genetic algorithm.